2003
DOI: 10.1002/jcp.10411
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of proliferation and induction of apoptosis in breast cancer cells by the epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor ZD1839 (‘Iressa’) is independent of EGFR expression level

Abstract: High expression of the epidermal growth factor receptor (EGFR) in breast carcinoma confers a growth advantage to the tumor cells. The EGFR tyrosine kinase inhibitor (EGFR-TKI) ZD1839 ('Iressa') has clinical activity in a wide range of tumor types, although the mechanism(s) by which it exerts its antitumor activity effects remain unclear. We analyzed the ability of ZD1839 to induce apoptosis and/or inhibition of proliferation in breast carcinoma cell lines, as well any association between this ability and the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
96
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 115 publications
(112 citation statements)
references
References 39 publications
15
96
1
Order By: Relevance
“…In agreement with these findings, co-expression of EGFR, ErbB-2 and ErbB-3 was also found to have a negative synergistic effect on patient outcome, independent of tumor size or lymph node status [9]. Different anti-EGFR agents, including the EGFR tyrosine kinase inhibitor (EGFR-TKI) gefitinib (ZD1839, Iressa), have shown to inhibit the growth of human breast carcinoma cells [10][11][12][13][14]. We and other research groups have demonstrated that breast cancer cell lines with high levels of expression of ErbB-2 are more sensitive to gefitinib as compared with ErbB-2-negative cells [11][12][13][14].…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…In agreement with these findings, co-expression of EGFR, ErbB-2 and ErbB-3 was also found to have a negative synergistic effect on patient outcome, independent of tumor size or lymph node status [9]. Different anti-EGFR agents, including the EGFR tyrosine kinase inhibitor (EGFR-TKI) gefitinib (ZD1839, Iressa), have shown to inhibit the growth of human breast carcinoma cells [10][11][12][13][14]. We and other research groups have demonstrated that breast cancer cell lines with high levels of expression of ErbB-2 are more sensitive to gefitinib as compared with ErbB-2-negative cells [11][12][13][14].…”
Section: Introductionmentioning
confidence: 65%
“…Different anti-EGFR agents, including the EGFR tyrosine kinase inhibitor (EGFR-TKI) gefitinib (ZD1839, Iressa), have shown to inhibit the growth of human breast carcinoma cells [10][11][12][13][14]. We and other research groups have demonstrated that breast cancer cell lines with high levels of expression of ErbB-2 are more sensitive to gefitinib as compared with ErbB-2-negative cells [11][12][13][14]. However, clinical studies of gefitinib in breast cancer resulted in few clinical responses and in a disease control rate of approximately 10% [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…As a negative control MDA-MB-231 cell line was used which does not express HER2 but expresses high levels of EGFR. [ 24 ] Cellular internalization of H-AFt-encapsulated-Gefi tinib was observed by confocal microscopy and compared to that of Gefi tinib. SKBR3 and MDA-MB-231 cells were treated with H-AFt-encapsulated-Gefi tinib, Gefi tinib, and H-AFt (5 × 10 −6 M ) for 24 h ( Figure 2 ; Section S2, Supporting Information).…”
Section: Communicationmentioning
confidence: 99%
“…Gefi tinib activity requires a phosphorylated (active) form of EGFR whereas MDA-MB-231 cells express nonphosphorylated EGFR and hence are not sensitive to this drug. [ 24 ] On the other hand, cancer cells that express low levels of EGFR together with overexpression of HER2 are sensitive to this drug and indeed, high sensitivity of SKBR3 cells to Gefi tinib was observed. [ 24,25 ] HER2 remains the preferred dimerization partner of other ErbB receptors.…”
Section: Communicationmentioning
confidence: 99%
See 1 more Smart Citation